Ona zashchishchaet rodinu - Ermler, Fridrikh (Soviet Union : Central Art Film studios USSR, 1943)
This is the story of Vera Maretskaya who joins the Soviet war effort during the Second World War in order to take revenge on the Nazi forces who destoryed everything she cared for. She witnesses her husband being killed in combat, her toddler run over by a German tank, and her village is commandeered by Nazi forces. She organizes the surviving locals into a guerilla band; she locates the Nazis responsible for the atrocity and kills them in as brutal a manner as possible. The violence the killing scenes was so intense that Americans never saw a complete print of the film. The critics who gave positive reviews to the movie in US at the time of its release were some of the first targets of the Red Scare in 1950s.
Duration: 01:14:00
With dubbing in English
Keywords: Fiction films